Energy and Economic Analysis of Curved, Straight, and Spiral Flow Flat-Plate Solar Water Collector. (7th July 2021) - Muthuraman, U.; Shankar, R.; Nassa, Vinay Kumar; Karthick, Alagar; Malla, Chandrabhanu; Kumar, Amit; Kumar, P. Manoj; Rahim, Robbi; Bharani, Murugesan
Abstract : In this work, the solar water collector flow tube geometry is modified as curved and spiral to enhance the system's performance. The investigation is carried out experimentally under the meteorological conditions of the Kovilpatti region (9°10 ′ 0 ″ N, 77°52 ′ 0 ″ E), Tamil Nadu, India. The flow pipes of the solar water heater are made of copper material which has higher thermal conductivity to recover the water heat as thermal energy. The influence of the mass flow rate (MF) on the flow pipes with respect to the surface temperature for various configurations of the flow tubes is investigated. The two MFs of 0.0045 kg/s and 0.006 kg/s are tested. The MF of 0.006 kg/s yields the maximum efficiency of 73% compared to the other MF. The straight, curved, and spiral tubes yielded the maximum efficiency of 58%, 62%, and 69%, respectively, at 0.0045 kg/s. Similarly, the MF of 0.006 kg/s obtained an efficiency of 62%, 65%, and 73% for straight, curved, and spiral flow tubes, respectively. The economics and exergy of the system are analyzed. The maximum exergy efficiency of the collector is estimated to be 32% for the MF of 0.0045 kg/s for the spiral flow collector, and for the 0.006 kg/s MF, the obtained exergy efficiency is 27% for the spiral flow water heater. The economic analysis revealed that the expense is $0.0608 and $0.0512 worth of hot water produced for the domestic space heating.